Using a mixed method audit to inform organizational stress management interventions in sport - Rumbold, J. L.; Fletcher, D.; Daniels, K. (Psychology of Sport and Exercise, 2018)
Objectives: The purposes of this study were twofold: to conduct a mixed method organizational-level stress audit within a sport organization and to explore recommendations for organizational stress management. Design and method: Semi-structured interviews, focus groups and surveys were conducted with 47 participants (professional sportsmen, coaches, sport science support and administrative staff) who represented a professional sport organization. Content analysis was employed to analyze the data. Results and conclusions: The findings indicated a wide range of organizational stressors (e.g., cultural and academy issues), appraisals and coping behaviors (e.g., emotion-focused behaviors), and stressor outcomes (e.g., emotional responses) for sport performers. Content analysis and survey data supported the categorization of stress management recommendations at both an individual- (e.g., coping education) and organizational-level (e.g., improving communication channels) for particular target groups (e.g., players, staff, team). The identification of stress audit factors and recommendations have important implications for the optimization of organizational functioning within professional sport. Consistent with organizational psychology research, applied considerations for mixed method and multi-level intervention approaches are discussed.